IMPLEMENTASI KURIKULUM 2013 BAGI GURU KIMIA DI SMA NEGERI SEKOTA BENGKULU - Ahaky Roza Clorawati; Salastri Rohiat; Hermansyah Amir (ALOTROP, 2017)
[IMPLEMENTATION OF 2013 CURRICULUM FOR CHEMICAL TEACHERS IN SMA Negeri AT BENGKULU ] This research is a description research conducted from SMA Negeri 1 to SMA Negeri 10 Kota Bengkulu for chemistry teacher in 2016/2017 academic year. This study aims to describe the implementation of the 2013 curriculum for chemistry teachers in the SMA Negeri in Bengkulu City. The population of this research is all the chemistry teachers who teach in ten SMA Negeri in Bengkulu consisting of 42 teachers. Samples were taken by proportional random sampling technique as much as 20%, but the samples taken are teachers who have implemented the curriculum 2013. Obtained final sample of 26 teachers. In this study, a questionnaire was used to collect data, including indicators of the overall implementation of the curriculum, scattered on 53 points of statement, using Likert Scale with a score of 1 to 4. which was then processed using Statistical Product Service Solution(SPSS)16 program. The results showed that the implementation of the 2013 curriculum, the average percentage of teachers who have implemented is 66.67% with the category mostly implemented. Specifically that is, planning obtained at 65,385%, implementation obtained at 57,692%. and assessment of learning result obtained at 76,923% with category mostly executed.